Effect of honey on nocturnal cough among children in Taif city - Al-Juaid, Hanan; AlJuaid, Aljwharah; Abuharba, Walaa; Abouhamda, Ayman (International Journal Of Community Medicine And Public Health, 2018)
Background: Nocturnal cough is a common disturbing symptom that affects children during upper respiratory tract infections and can have a major negative impact on child and parents’ sleep quality. Many pharmaceutical medications, herbal regimens, and non-pharmaceutical advice are prescribed to reduce nocturnal cough. The aim of this research was to study the impact of honey on nocturnal cough in children. Methods: A descriptive study was conducted on 226 children in Taif city, KSA using a pre-prepared questionnaire to assess the cough severity and response to honey in comparison to other treatment modalities. Data collected were then analyzed using SPSS software. Results: The study was conducted on 226 children (51.77% were females). Children who used honey were significantly older (mean age 7.64±3.8 years) than those who used medications (mean age 6.98±60) (p=0.025). Children who used honey had a higher prevalence of headache (p=0.001) and malaise (p<0.001) than children who did not receive honey. The use of honey was also significantly associated with high cough severity scores. The use of honey seemed to significantly reduce both the cough severity score and combined severity scores, with odd’s ratios of 0.46 and 0.19, respectively (p=0.020 and <0.001). However, it was associated with fewer satisfaction rates and fewer intentions to re-use in next attacks (p=0.025). Conclusions: Honey has a beneficial effect on treating nocturnal cough in children. It decreases the severity of cough as well as the frequency of cough. It is commonly used among older Saudi children who have cough associated with malaise and fever. However, it is not satisfactory for patient and parental relief in Taif city because it doesn’t improve the sleep quality of patients or parents.